2014
DOI: 10.14366/usg.14011
|View full text |Cite|
|
Sign up to set email alerts
|

Benign core biopsy of probably benign breast lesions 2 cm or larger: correlation with excisional biopsy and long-term follow-up

Abstract: Purpose:To evaluate the accuracy of benign core biopsy of probably benign breast lesions (category 3) 2 cm or larger on the basis of excisional biopsy and long-term follow-up. Methods:We retrospectively reviewed 146 category 3 lesions in 146 patients 2 cm or larger which were diagnosed as benign by ultrasound (US)-guided core biopsy. Patients were initially diagnosed as benign at core needle biopsy and then followed up with excisional biopsy (surgical excision, n=91; US-guided vacuum assisted excision, n=35) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Recently, Jung et al 18 reported that some growing masses on follow-up sonography, which had first been diagnosed as benign tumours by ultrasound-guided core biopsy, were confirmed as benign or malignant phyllodes tumours by subsequent excisional biopsy. In our series, 10 cases had been initially diagnosed as fibroadenoma by ultrasound-guided core biopsy and were finally confirmed as phyllodes tumours by complete removal (benign phyllodes tumour: 7/31, aggressive phyllodes tumour: 3/15).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jung et al 18 reported that some growing masses on follow-up sonography, which had first been diagnosed as benign tumours by ultrasound-guided core biopsy, were confirmed as benign or malignant phyllodes tumours by subsequent excisional biopsy. In our series, 10 cases had been initially diagnosed as fibroadenoma by ultrasound-guided core biopsy and were finally confirmed as phyllodes tumours by complete removal (benign phyllodes tumour: 7/31, aggressive phyllodes tumour: 3/15).…”
Section: Discussionmentioning
confidence: 99%
“…Familiarity with the BI-RADS classification is a crucial step for correctly determining imaging–pathology similarity for all accessible modalities [ 11 , 13 ]. According to the new BI-RADS update, the likelihood of malignancy within category 4 (suspicious) ranges from 2 to 95% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…When concern regarding a dissonant benign biopsy exists, immediate communication within the healthcare team about the discrepancy and best biopsy method is necessary [ 11 ]. On the other hand, the high-risk/borderline category is not malignant but presents a high lifetime malignancy risk along with the ongoing controversy of whether surgical or oncological treatment is the appropriate management [ 13 ]. According to the Mayo Clinic, a large cohort study found an accumulative risk of breast cancer development in those with high-risk lesions (such as ADH), and 25 years after the first biopsy, malignancy developed in 30% of the women with these lesions [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A later study in 2005 with long-term follow-up reported a false-negative rate of 3.7% for 14-gauge US-guided CNB, with three delayed diagnoses of cancer occurring at the site of prior CNB [ 5 ]. However, recent studies published in the last decade have reported slightly lower false-negative rates of US-guided CNB, ranging from 0.1% to 2.5%, with most cases identified because of discordance between imaging results and CNB histologic findings ( Table 1 ) [ 7 - 11 , 14 , 15 ]. The reported underestimation rate of high-risk lesions through US-guided CNB, a category primarily composed of atypical ductal hyperplasia (ADH) lesions in most studies, ranges from 24.5% to 65% [ 7 , 8 , 10 , 16 ].…”
Section: Review Of Us-guided Breast Biopsymentioning
confidence: 99%